179k views
4 votes
Rewrite the function f (x) = 3 (x - 1)^2 – 2 in the form f(x) = ax^2+bx+c

User Ashik
by
4.9k points

2 Answers

0 votes
3(x-1)^2-2
3(x^2-2x-1)-2
3x^2-6x-3-2
F(x) = 3x^2-6x-5
User Artem Lopatiy
by
4.3k points
1 vote

Answer: 3x^2-6x+1

Explanation:

In this question, you just have to foil out the expression and multiply things out to get the results. Rewrite it if you need so you can caluate it like what I did in this picture.

Rewrite the function f (x) = 3 (x - 1)^2 – 2 in the form f(x) = ax^2+bx+c-example-1
User CronosNull
by
4.7k points